2020
DOI: 10.1186/s12967-020-02339-3
|View full text |Cite
|
Sign up to set email alerts
|

Why tocilizumab could be an effective treatment for severe COVID-19?

Abstract: A severe pneumonia-associated respiratory syndrome caused by a new coronavirus was identified in December 2019 , spread rapidly and has become a world-wide public health challenge. About 25% of COVID-19 patients experienced severe complications including acute respiratory distress syndrome (ARDS), and even progressed into an intensive care unit (ICU) admission and died. The exploration for the mortality causes and advancing novel therapeutic development of severe COVID-19 is crucial at the moment. The biopsy s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

17
386
1
26

Year Published

2020
2020
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 403 publications
(430 citation statements)
references
References 9 publications
17
386
1
26
Order By: Relevance
“…The improvement in knowledge on COVID-19related ARDS pathogenesis has pointed out the central role of the abnormal immune response to SARS-CoV-2 leading to a massive release of pro-in ammatory mediators known as cytokine release storm [52,53]. This has actually paved the way for the use of biological drugs and small molecules in the treatment of the most severe subsets of COVID-19 [13,[54][55][56][57][58][59]. Although the apparent bene cial therapeutic effects of immunomodulatory agents cannot be translated into any speculation on their prophylactic role, the possibility that chronic use of ts/bDMARDs may dampen exaggerated immune reactions, thus mitigating COVID-19 progression into more symptomatic patterns, deserves further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…The improvement in knowledge on COVID-19related ARDS pathogenesis has pointed out the central role of the abnormal immune response to SARS-CoV-2 leading to a massive release of pro-in ammatory mediators known as cytokine release storm [52,53]. This has actually paved the way for the use of biological drugs and small molecules in the treatment of the most severe subsets of COVID-19 [13,[54][55][56][57][58][59]. Although the apparent bene cial therapeutic effects of immunomodulatory agents cannot be translated into any speculation on their prophylactic role, the possibility that chronic use of ts/bDMARDs may dampen exaggerated immune reactions, thus mitigating COVID-19 progression into more symptomatic patterns, deserves further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…A study published in April 2020 reported that 21 severe or critical COVID-19 patients in China were treated with the compound, with 20 of them recovered at the time of publication and 1 on the way to recovery (but still in ICU). Encouraged by these results, a larger multicenter clinical trial was launched (ChiCTR2000029765) and had about 500 patients treated with tocilizumab already enrolled [109,110].…”
Section: Tocilizumabmentioning
confidence: 99%
“…Tocilizumab, that targets IL-6 receptors, was suggested to be effective on clinical evolution as well as on immune dysregulation. 6 After a single TCZ injection, serum IL-6 level first increases rapidly before decreasing. In the absence of significant clinical improvement with persistence of an elevated IL-6 level, a second and a third dose of TCZ can be administered after 12 and 24-36 hours respectively.…”
mentioning
confidence: 99%